Pengaruh Pencucian Darah Domba dengan NaCl 0,85% Terhadap Pertumbuhan Bakteri Neisseria gonorrhoeae Pada Media CAP - Agrijanti, Agrijanti; Intan Suryawatie Yomo, Meidiana; Khusuma, Ari; Kusuma Dewi, Lale Budi (Jurnal Analis Medika Biosains (JAMBS), 2022)
Neisseria gonorrhoeae is a fastidious organism. The growth medium for the bacterial culture of Neisseria gonorrhoeae is a Chocolate Agar Plate (CAP) medium enriched with additional nutrients such as sheep blood, vancomisin, nystatin, and isovitaleX. in general, the making of  CAP  is not washed (defibrinated) the sheep blood, in this research, the sheep blood was washed (defibrinated) with NaCl 0.85%. The purpose of the research is to determine the effect of washed sheep blood with NaCl 0.85% on the growth of Neisseria gonorrhoeae in CAP. The method of this research is a pre-experiment conducted in a laboratory to find out a symptom or effect that arises as a result of the treatment of the sample. The treatment in this research is CAP washed of sheep blood and CAP with unwashed sheep blood as a control. The result is the colonies that grew on CAP treatment were better than colonies that grew on CAP control. The conclusion of this research is there is an effect of washed sheep blood with NaCl 0.85% on the growth of Neisseria gonorrhoeae in CAP medium.